O papel de relações de controle de estímulos na aprendizagem relacional de indivíduos com deficiência mental e com desenvolvimento típico - Grisante, Priscila Crespilho (2007)
Accordingly to stimulus control topography coherence theory the variability found in some stimulus equivalence experimental studies could be reduced or eliminated by a larger experimental control upon the controlling relations established on conditional relations training. Therefore, this research had as general goals: 1) investigating emergence of classes of equivalence stimuli between visual abstract stimuli, using a mask procedure in teaching conditional discriminations (to induce controlling relations by selection and by rejection) in preschool children and in individuals with Down Syndrome (participants up to now not studied with this procedure) and 2) verifying if the controlling relations involved in teaching of conditional discriminations coincided with those planned by the researcher. Two six year old typically developing children took part in Experiment 1 consisted by the phases: 1) pretraining; 2) teaching the conditional relations AB, BC, CD; 3) testing relations DA, AD, CA, AC, DB, BD and 4) testing to verify the controlling relations involved on baseline. A computer presented stimuli and recorded responses. For one of the participants, one-node equivalence classes were established and the controlling relations were consistent with those planned (both, by selection and rejection). The second paticipant did not show the expected emergent performances and showed inconsistent stimulus control. Experiment 2 was carried out with a child and an adolescent with Down Syndrome and consisted of the phases: 1) pretraining; 2) teaching the conditional relations AB, BC; 3) testing relations CA, AC and 4) testing to verify the controlling relations. In Experiment 2 none of the subjects showed the expected emergent performances in three presentations of test sessions. Moreover, they showed acquisition of control relations inconsistent with those planned. The results support the hypothesis that the variability found in stimulus equivalence research can be explained by the acquisition of different controlling relations throughout the teaching and also suggest that the kind of procedure employed on tests to verify the controlling relations can be efficient to identify these stimulus control relations.